2007
DOI: 10.1073/pnas.0606206104
|View full text |Cite
|
Sign up to set email alerts
|

Parasite-intrinsic factors can explain ordered progression of trypanosome antigenic variation

Abstract: Pathogens often persist during infection because of antigenic variation in which they evade immunity by switching between distinct surface antigen variants. A central question is how ordered appearance of variants, an important determinant of chronicity, is achieved. Theories suggest that it results directly from a complex pattern of transition connectivity between variants or indirectly from effects such as immune cross-reactivity or differential variant growth rates. Using a mathematical model based only on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(90 citation statements)
references
References 58 publications
7
83
0
Order By: Relevance
“…Previous efforts to generate dynamical models of antigenic variation have taken a range of approaches that are complementary to our work. Some models have not considered cross-reactive immunity and instead focused on other aspects of infection dynamics such as the ordered appearance of variants, differentiation of parasites during the course of infections and linking the within and between host dynamics of the pathogen [16][17][18]22,[25][26][27]. Other models have explicitly incorporated crossreactive immunity and the breadth of immune responses but have focused on diseases such as HIV that directly subvert the immune system leading to qualitatively different dynamics [20,21,41].…”
Section: Discussionmentioning
confidence: 99%
“…Previous efforts to generate dynamical models of antigenic variation have taken a range of approaches that are complementary to our work. Some models have not considered cross-reactive immunity and instead focused on other aspects of infection dynamics such as the ordered appearance of variants, differentiation of parasites during the course of infections and linking the within and between host dynamics of the pathogen [16][17][18]22,[25][26][27]. Other models have explicitly incorporated crossreactive immunity and the breadth of immune responses but have focused on diseases such as HIV that directly subvert the immune system leading to qualitatively different dynamics [20,21,41].…”
Section: Discussionmentioning
confidence: 99%
“…However, as parasite numbers increase, an unidentified parasite-derived signal (stumpy induction factor; SIF) stimulates growth arrest in G1 (Vassella et al, 1997). This quorum sensing (QS) mechanism induces the developmental switch to morphologically stumpy forms, which do not divide, thereby limiting the increase in parasite numbers and promoting the generation of a chronic infection (Lythgoe et al, 2007). Although stumpy forms are irreversibly committed to cell division arrest in the bloodstream, this does not represent a simple example of self-destructive cooperation, as seen in some bacterial populations (Ackermann et al, 2008;Gardner and Kummerli, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Various other mechanisms have been suggested in the literature [60][61][62]. A model by Recker et al [63] has shown that, e.g., transient cross-reactive immune responses are able to orchestrate realistic within-host antigenic variation.…”
Section: Growth Rate Differences Related To Variant Surface Antigen Ementioning
confidence: 99%